Comparison of the Percentage of Voids following Root Canal Obturation with Gutta Percha and AH26 Sealer Using Four Different Sealer Placement Techniques - Mohammad reza Nabavizadeh; Fariborz Moazami; Mehdi Sedigh Shamsi; Zahra Emami (Islamic Dental Association of Iran, 2013)
Background and Aim: Different techniques are employed for sealer placementinto the root canal system. The purpose of this study was to compare the percentage of voids following root canal obturation with gutta percha and AH26 sealer using four different sealer placement techniques .   Materials and Methods: In this laboratory experimental study, root canals of 50 mandibular second premolars were prepared using the step-back technique. The teeth were assigned to 4 experimental groups of 10 and one control group based on sealer placement technique. After sealer application and canal obturation with lateral condensation technique, specimens were horizontally cut into 3 mm slices. Sections were evaluated under a digital microscope at 150X magnification for void detection in apical, middle and coronal thirds. Kruskal Wallis and Bonferroni tests were applied to compare the percentage of voids between different groups .   Results: No significant difference was found in void percentage in one-thirds or total sections between the four methods (P=0.276 ).   Conclusion: Overall, no significant difference was noted in void percentage between the four techniques of sealer placement .